Operated case of tubercular meningitis with hydrocephalus in an immunocompromised patient and acute abdomen-management controversy: a case report - Nath, Amar (International Surgery Journal, 2021)
Tuberculosis is a very common infectious disease in developing countries like India. Most common form includes pulmonary tuberculosis. Other common forms are tubercular meningitis and intestinal tuberculosis. Hydrocephalus is one of the commonest complications of tubercular meningitis. We present a HIV positive case who had tubercular meningitis with hydrocephalus and was operated for ventriculoperitoneal shunting, later developed intestinal tuberculosis with perforation peritonitis. The presentation of an acute abdomen with a ventriculo-peritoneal shunt requires skillful diagnostic workup and management. Apart from complications caused by the shunt, primary abdominal pathological conditions must be taken into consideration. Tuberculosis has multiple presentations all of which should be kept in mind.